KAPASITAS INFILTRASI DI KAWASAN PERKEBUNAN KALIBENDO KABUPATEN BANYUWANGI - , AHMAD RINDOAN, Ir. Sri Astuti Soedjoko ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Inflitration is an entry process of water to the soil. This is influenced by many factors such as land use, , biological activity, organic material, vegetation, and undergrowth species. Kalibendo plantation is ecologically potential to provide environmental services such as water within water yield concept. This research aims to obtain information on infiltration capacity in plantation which was influenced by the density of undergrowth species. The infiltartion capacit measurement was conducted in rubber, clove and cofee plantation using double ring infiltometer. The e Result showed that the average infiltration capacity for each plantation was 34,7 mm/hour in rubber (classified as medium), 84 mm/hour in clove (classified as fast medium) and 74 mm/hour in cofee (classified as fast medium). According to the undergrowth species, the greatest capacity was found in rubber plantation area which was 68 mm/hour, low density was 68 mm/hour in clove area, and medium density was 84 mm/hour in coffe area. xistence of lower plants as ground should be maintened in order to support soil and water conservation efforts in plantation areas of Kalibendo. The information of infiltration capacity is important reference to the plantation management through water and soil conservation planing.